Corporate Revenue Consultancy Training Uncovers Operational Ethical Industry Gaps: Pelatihan Konsultasi Pendapatan Perusahaan Mengungkap Kesenjangan Operasional Etika Industri - Althaf Naufal Ghozi E; Parade Firman Abadi (International Consortium of Education and Culture Research Studies, 2024)
General Background Taxation constitutes a primary state financial source, requiring stringent regulatory adherence and competent administration to support national development. Specific Background Financial consultants function as crucial intermediaries connecting regulatory authorities with taxpayers, necessitating comprehensive legal preparation for prospective practitioners entering this sector. Knowledge Gap Despite structured academic preparations, significant discrepancies persist separating theoretical regulations from actual field implementations, particularly concerning technology utilization and client transparency. Aims This study evaluates an undergraduate legal preparation program to identify workflow challenges and bridge the division separating academic statutes from professional reality. Results Qualitative observational analysis indicates that while trainees successfully executed fundamental tasks including transaction auditing and calculating various income deductions, substantial practical barriers emerged. Practitioners frequently encountered clients possessing low fiscal literacy and utilized outdated manual reporting systems, directly contradicting modern modernization frameworks. Furthermore, trainees faced internal constraints, specifically limited exposure to high-risk document management and insufficient comprehensive calculation materials. Novelty This research maps specific socio-technical and ethical divergences within regulatory advising, isolating precise barriers complicating the transition from academic theory to professional execution. Implications Academic institutions and advising firms must collaborate to provide rigorous practical simulations, integrate advanced reporting software, and allocate diverse risk-based responsibilities to secure future workforce readiness. Highlights: Significant discrepancies exist separating academic tax regulations from actual professional executions. Manual reporting systems combined with low client literacy severely hinder administrative modernization. Restricted access regarding high-risk assignments limits comprehensive workforce development during legal preparations. Keywords: Tax Law, Legal Education, Professional Ethics, Reporting Technology, Workforce Readiness